Exploring Deictic Expressions In The Sigale-Gale Story: A Pragmatic Analysis - Simbolon, Lasyuli; Fithriani, Rahmah; Pardi, Pardi (Lembaga Riset dan Inovasi Almatani, 2026)
This study explores deictic expressions in the Sigale-Gale story, a traditional Batak Toba folklore, using a pragmatic approach. Deictic expressions are context-dependent linguistic elements that indicate participants, time, place, discourse, or social relationships, and they play a crucial role in constructing meaning in narrative texts. The study aims to identify and analyze the types of deixis used in the story and to explain their functions in relation to context and culture. A qualitative descriptive method was employed, with the story serving as the primary data source. Data were collected through the documentation method and analyzed using classification based on five deixis categories: person, place, time, discourse, and social deixis. The findings reveal that person deixis is the most frequently used type, particularly third-person pronouns, reflecting the narrative focus on characters and events. Place and time deixis are also significant, helping to establish spatial and temporal frameworks that guide readers’ understanding of the story. Discourse and social deixis, though less frequent, contribute to textual coherence and convey cultural norms, such as social hierarchy and kinship relations. Overall, the analysis demonstrates that deictic expressions in the Sigale-Gale story function not only as linguistic devices but also as tools for cultural representation and narrative cohesion. This study highlights the importance of pragmatic analysis in traditional folklore, offering insights into how context and culture interact in storytelling. The results may serve as a reference for further research on deixis in other local narratives.